Challenge and Transformation: The Innovative Role of Supervisors in 21st Century Educational Supervision - Ayu Puspitasari; Dwi Utari; Muhammad Rohim; Sudadi Sudadi (Journal on Education, 2023)
The role of educational supervisors has evolved to become more proactive, innovative and agile in response to the needs and demands of modern education. In the 21st century, supervisors face complex challenges, including rapid technological change, dynamic curricula, inclusiveness and diversity, increased human resources, holistic evaluation and changing roles. This research aims to find out the extent of the supervisor's transformation role and what challenges surround educational supervision in the 21st century. The research method used a descriptive qualitative approach. The results showed that to overcome the challenges of the 21st century, a new round of transformed supervisor roles to adopt innovative strategies such as integrating technology in supervision, adaptive curriculum development, continuous training and support for teachers, collaborative approaches, and a balance between technological and humanist approaches. The use of virtual-based supervision, collaborative approaches in developing learning strategies, and the application of innovative evaluation methods are some of the strategies that can be applied by supervisors. In addition, supervisors must be competent and skillful in reading signs of progress over time and play an active role in the creation of a curriculum that is adaptable and can respond quickly to evolving educational needs. Overall, supervisors must adapt, upgrade their competencies and adopt innovative approaches in the supervision process to ensure education is relevant, inclusive and adaptive to the demands of the times.